Religion Humanitarian Values And Cultural Diversity: Fostering Inclusive Societies Through Ethical Integration - Muh Habibulloh (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
: In the era of globalization, the interplay between religion, humanitarian values, and cultural diversity has become increasingly significant in shaping inclusive and equitable societies. Religion provides moral and ethical foundations that guide social norms, while humanitarian values emphasize empathy, dignity, and justice across cultural and social differences. Cultural diversity, meanwhile, enriches human interaction but also introduces challenges when differences lead to miscommunication or conflict. This study employs a library research method with a descriptive-analytical approach to explore how ethical integration among these dimensions fosters social cohesion and inclusivity. Findings reveal that societies thriving on inclusivity promote interfaith dialogue, humanitarian education, and multicultural understanding through participatory governance. Moreover, aligning religious teachings with universal humanitarian values helps address social inequalities and cultural tensions. The study concludes that ethical integration across these domains serves as a strategic pathway for cultivating tolerant, just, and sustainable multicultural societies